Performance Comparison Between Plasma and Stool Methylated SEPT9 Tests for Detecting Colorectal Cancer - Liu, Yi; Zhao, Guodong; Miao, Jin; Li, Hui; Ma, Yong; Liu, Xiaoyu; Li, Shiming; Zhu, Yun; Xiong, Shangmin; Zheng, Minxue; Fei, Sujuan (Frontiers in Genetics, 2020)
Colorectal cancer (CRC) is the most common type of malignancies of the gastrointestinal tract worldwide. Plasma methylated SEPT9 test has been used clinically for CRC screening for several years, but the study about the performance comparison between plasma and stool has rarely been reported. In this study, 124 plasma samples, 100 stool samples, and 60 sets of plasma and paired stool samples were collected and tested by a methylated SEPT9 test in three PCR replicates. The results indicated methylated SEPT9 levels in stool samples were significant higher than those in plasma samples (p<0.0001). When a plasma sample was called positive if 1 out of 3 PCR replicates was positive and a stool sample was called positive if 3 out of 3 PCR replicates were positive with a mean Cp value of less than 40.0, stool methylated SEPT9 test achieved similar sensitivity (83.3% vs 85.6%) and specificity (92.1% vs 90.1%) to those by plasma methylated SEPT9 test, and the overall concordance rate is 78.3%. However, stool methylated SEPT9 test showed 35.9% and 7.9% improvement in detecting advanced adenomas (AA) and stage I-II CRC in comparison to plasma methylated SEPT9 test. The AUC for plasma methylated SEPT9 and stool methylated SEPT9 in detecting CRC were 0.885 (95% CI: 0.832 – 0.938) and 0.935 (95% CI: 0.895 – 0.975), respectively. In conclusion, stool methylated SEPT9 test showed higher sensitivities for detection AA and early stage CRC compared with plasma methylated SEPT9 test, and stool methylated SEPT9 test may be a more suitable tool for early stage CRC screening.